A practical guide to inference in simulation models - Thomas Brenner; Claudia Werker (Max Planck Institute of Economics, 2006)
This paper introduces a categorization of simulation models. It provides an explicit overview of the steps that lead to a simulation model. We highlight the advantages and disadvantages of various simulation approaches by examining how they advocate different ways of constructing simulation models. To this end, it discusses a number of relevant methodological issues, such as how realistic simulation models are obtained and which kinds of inference can be used in a simulation approach. Finally, the paper presents a practical guide on how simulation should and can be conducted.
Keywords: B41; B52; C63; 330; Methodology; Simulation Models; Practical Guide